Development of 2-oxindolin-3-ylidene-indole-3-carbohydrazide derivatives as novel apoptotic and anti-proliferative agents towards colorectal cancer cells. (1st January 2021) - Eldehna, Wagdy M.; Abo-Ashour, Mahmoud F.; Al-Warhi, Tarfah; Al-Rashood, Sara T.; Alharbi, Amal; Ayyad, Rezk R.; Al-Khayal, Khayal; Abdulla, Maha; Abdel-Aziz, Hatem A.; Ahmad, Rehan; El-Haggar, Radwan
Abstract: Mitochondrial anti-apoptotic Bcl2 and BclxL proteins, are overexpressed in multiple tumour types, and has been involved in the progression and survival of malignant cells. Therefore, inhibition of such proteins has become a validated and attractive target for anticancer drug discovery. In this manner, the present studies developed a series of novel isatin–indole conjugates (7a-j and 9a-e ) as potential anticancer Bcl2 and BclxL inhibitors. The progression of the two examined colorectal cancer cell lines was significantly inhibited by all of the prepared compounds with IC50 ranges 132–611 nM compared to IC50  = 4.6 µM for 5FU, against HT-29 and IC50 ranges 37–468 nM compared to IC50  = 1.5 µM for 5FU, against SW-620. Thereafter, compounds 7c and 7g were selected for further investigations. Interestingly, both compounds exhibited selective cytotoxicity against both cell lines with high safety to normal fibroblast (HFF-1). In addition, both compounds 7c and 7g induced apoptosis and inhibited Bcl2 and BclxL expression in a dose-dependent manner. Collectively, the high potency and selective cytotoxicity suggested that conjugates 7c and 7g could be a starting point for further optimisation to develop novel pro-apoptotic and antitumor agents towards colon cancer.